Do egalitarian societies boost fertility? - Gustav Feichtinger; Alexia Prskawetz; Andrea Seidl; Christa Simon; Stefan Wrzaczek (Austrian Academy of Sciences (ÖAW), Vienna Institute of Demography (VID), 2013)
In general, the spreading of egalitarian family values has often been associated with a decline in fertility. However, recently a rebound in fertility has been observed in several industrialized countries. A possible explanation of this trend may be the spread of egalitarian values that induced institutional changes - such as expansion of child care facilities and father leave - fostering the combination of parenthood and the egalitarian lifestyle. In our paper we build up a formal model to study the diffusion from traditional to egalitarian gender-behavior and its impact on fertility. We find that the long-run development of the total fertility within a population not only depends on the pace of diffusion of egalitarianism and the extent to which social interactions affect the egalitarians' birth rates, but also on the initial number of traditionalists and egalitarians. We show under which conditions a fertility decline is followed by a subsequent recovery.
Keywords: 300; Egalitarianism; family models; diffusion; fertility; Gleichberechtigung; Fertilität; Industrieländer; Welt